Clinical Effects of Long-term Administration of Pranlukast, a Leukotriene Receptor Antagonist, on Adult Patients with Bronchial Asthma - Horiguchi, Takahiko; Tachikawa, Soichi; Kondo, Rieko; Shiga, Mamoru; Hirose, Masahiro; Ito, Tomohiro (Arzneimittelforschung, 2003)
Eighty-one adult patients with bronchial asthma who suffered from an unstable peak expiratory flow rate (PEFR) and asthmatic attacks that developed at irregular intervals in spite of inhaling beclometasone dipropionate (CAS 5534-09-8, BDP) in excess of 400 µg/day were treated with pranlukast (CAS 103177-37-3, Onon®) 450 mg/day for 1 to 2 years and the clinical effects of its long-term administration were studied.The patients were divided into 3 groups: Group I with drug effect seen on peak expiratory flow rate (PEFR) in a short-term; Group II showing long term PEFR improvement; and Group III with no sustained improvement in PEFR. Those in the first two groups continued oral medication for 2 years, while those of the third group withdrew from medication after one year and their clinical course was observed. The evaluation parameters were: PEFR, frequency of β2-stimulant inhalation, number of night time visits to health service facilities, quantity of inhalation steroids used, amount of oral steroids used at fixed intervals, peripheral eosinophil count, serum eosinophil cationic protein (ECP) concentration and FEV1.0.In Group I, the frequency of β2-stimu-lant inhalation, number of night time visits to health service facilities, quantity of inhalation steroids used, and the amount of oral steroids used at fixed intervals were reduced; and after two years, the frequency of β2-stimulant inha-lation and quantity of inhalation steroids used were further reduced. In Group II, reductions were seen in the peripheral eosinophil count and serum ECP level. The asthmatic severity shifted from step 3 to 2 in 12 patients and from step 4 to 3 in 4 patients in Group I; and from step 3 to 2 in 3 patients in Group II. In Group III, an increase in the number of night time visits to health service facilities after the medication was interrupted and a rise in the serum ECP concentration were recognized.
Keywords: Bronchial asthma; CAS 103177-37-3; Leukotriene receptor antagonist; Onon®; Pranlukast, long-term administration, patients